Adapting to climate change: An integrated biophysical and economic assessment for Mozambique - Arndt, Channing; Strzepek, Kenneth M.; Tarp, Finn; Thurlow, James; Fant, Charles; Wright, Len (Springer, 2011)
Mozambique, like many African countries, is already highly susceptible to climate variability and extreme weather events. Climate change threatens to heighten this vulnerability. In order to evaluate potential impacts and adaptation options for Mozambique, we develop an integrated modeling framework that translates atmospheric changes from general circulation model projections into biophysical outcomes via detailed hydrologic, crop, hydropower and infrastructure models. These sector models simulate a historical baseline and four extreme climate change scenarios. Sector results are then passed down to a dynamic computable general equilibrium model, which is used to estimate economy-wide impacts on national welfare, as well as the total cost of damages caused by climate change. Potential damages without changes in policy are significant; our discounted estimates range from US$ 2.3 to US $7.4 billion during 2003-2050. Our analysis identifies improved road design and agricultural sector investments as key 'no-regret' adaptation measures, alongside intensified efforts to develop a more flexible and resilient society. Our findings also support the need for cooperative river basin management and the regional coordination of adaptation strategies.